Internet and Video Games: Causes of Behavioral Disorders in Children and Teenagers - Virginia Lérida-Ayala; José Manuel Aguilar-Parra; Rocío Collado-Soler; Marina Alférez-Pastor; Juan Miguel Fernández-Campoy; Antonio Luque-de la Rosa (Children, 2022)
Even though video games have been present among children for many years, children are using them more continuously and in an abusive and indiscriminate way nowadays because of the “technological boom”. It is affecting the behavior of children and adolescents. This is the reason why we are carrying out this systematic review. The main objective of this article is to investigate literature that directly connects the continuous and undifferentiated use of video games with the emergence of behavioral disorders in children and young people. The PRISMA statement was followed in the process of this article. We used SCOPUS, Web of Science and PubMed as databases, moreover, we searched studies with a scoping review. The results indisputably supported six out of seven of our hypotheses. We find that the excessive use of video games causes addiction to technology, aggressive behaviors, sleep disorders, and poor school performance. In addition, it hinders social relationships and the development of emotional intelligence. To conclude, it is necessary to correctly use video games in particular, and technologies in general, adapting their content to children’s age, as well as the amount of time that they dedicate to use them.